The Effect Of Peer Group And Hedonistic Lifestyle Purchase Decisions On Iphone In Jepara City Using Behavioral Intention As A Mediating Variable - Jesica Anastasia Oktaviola; Mohamad Rifqy Roosdhani (Jurnal Economic Resource, 2026)
The purpose of this research is to ascertain the effect of peer groups and hedonistic lifestyle on iPhone purchases in Jepara City, with The role of behavioral intention in mediating variable. The research employs a quantitative approach using. Data analysis methods for examining the correlations between variables include partial least squares (PLS). The study's population include all iPhone users in Jepara City aged 15–40 years. Data were gathered via an online survey that used Google Forms, resulting in 210 respondents selected using the Rao Purba formula. The research instrument utilized a 1–10 Likert scale. The findings show that peer groups and hedonistic lifestyle have a significant and positive effect on purchase decisions as well as behavioral intentions. Additionally, it has been demonstrated that behavioral intention mediates the effect of peer groups and hedonistic lifestyle on iPhone purchase decisions.